PEDAGOGICAL COMPETENSE REQUIRED FROM THE DRIVING SCHOOL ENGINEER (PROFESSOR) - BUIMESTRU, Lilia (Acta et Commentationes, Sciences of Education, 2019)
this is being demanded and expected by the society. The given article points out the driving school engineer’s (teacher’s) professional training and development, established according to the competencies method. The demanded competences are highlighted here as follows: cognitive, psychosocial, managerial and psycho-pedagogical. In the article there is described an example of engineer’s training and reskilling (schooling to obtain a new professional qualification), which is determined by the specific of the profession, adapted to the driving school context, as part of the educational system. At the same time, in this work, there is exposed the vision of the continuous professional training, as a dynamic and constant process, which aims to ensure the career growth to the applicant.